2022
DOI: 10.3390/land11071117
|View full text |Cite
|
Sign up to set email alerts
|

Riverine Plastic Pollution in Asia: Results from a Bibliometric Assessment

Abstract: Rivers are important ecosystems, vital to the livelihoods of hundreds of millions of humans and other species. Despite their environmental, social, and economic importance, current use of rivers is unsustainable, due to a combination of solid waste and high levels of pollutants. Plastic materials are among the most predominant of such pollutants. Based on the need for additional research in this area, this study examines pressures put to rivers and explores trends related to riverine plastic pollution, with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…In addition, environmental issues such as health problems and food insecurity caused by pollution can have significant impacts on communities and further worsen poverty in areas where it is already difficult to earn a living or receive an education (Abideen et al , 2021; Kopittke et al , 2019; Tan and Kamaruddin, 2019). Significant gaps in legislation and standards are impeding the implementation of these changes and reflect the serious problems posed by plastic trash in Asian waterways (Leal Filho et al , 2022a). The adoption of the United Nation’s sustainable development goals (SDGs) in 2015 evoked a sense of optimism regarding their achievable implementation by the year 2030 (Leal Filho, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, environmental issues such as health problems and food insecurity caused by pollution can have significant impacts on communities and further worsen poverty in areas where it is already difficult to earn a living or receive an education (Abideen et al , 2021; Kopittke et al , 2019; Tan and Kamaruddin, 2019). Significant gaps in legislation and standards are impeding the implementation of these changes and reflect the serious problems posed by plastic trash in Asian waterways (Leal Filho et al , 2022a). The adoption of the United Nation’s sustainable development goals (SDGs) in 2015 evoked a sense of optimism regarding their achievable implementation by the year 2030 (Leal Filho, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…iv. Hydrocarbon designed spectral indices: These are indices based on user-friendly algorithms for the detection of hydrocarbons centered on their noticeable absorption features at 1730 and 2310 nm [153] . Plastics are largely hydrocarbons; therefore, hydrocarbon indices in combination with others have been successfully applied for the detection of plastic litter in water using hyperspectral images [42] .…”
Section: Remote Sensing (R ) Floating Plastic Debris Spectral Indicesmentioning
confidence: 99%
“…Plastics are largely hydrocarbons; therefore, hydrocarbon indices in combination with others have been successfully applied for the detection of plastic litter in water using hyperspectral images [42] . The following formula can be used to calculate the hydrocarbon index (HI) [153] :…”
Section: Remote Sensing (R ) Floating Plastic Debris Spectral Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that in the European environment 7 kg of microplastic per minute enters due to PCCP and cosmetics. Microplastic due to PCCP and Cosmetics is reported in the wastewater streams from households, hotels, hospitals, and sports facilities including beaches Leal Filho et al (2022), Habib et al (2020), Bansal (2020), Boucher and Friot (2017).…”
Section: Major Sources Of Environmental Microplasticsmentioning
confidence: 99%